GAP: an exploring picture of male and female students quantity gap at English Department, Tarbiyah Faculty, UIN Ar-Raniry - Khairil Razali (Englisia: Journal of Language, Education, and Humanities, 2015)
This study tried to explore the current facts of significant different between male and female students at university. This reality has been happening at most of major studies in the university. Therefore, the study would like to bring into an explanation of how the differences between male and female students in the classroom at English Department. The study applied documents analysis and interviews in collecting sufficient data to clearly picture the gaps of quantity, quality and impacts. Samples were selected randomly of the fourth and the sixth semester students where I was teaching courses. Moreover, the interviews were purposively selected which represented equal number of each class. As a result, some interesting basic facts show that there are quantitatively different of male and female students. As a matter of fact, it leads to major impacts in term of academic achievements and learning attitudes and interactions. The data show that female more advanced compared to male students. On the other hand, male students stated that they would be â€œreluctant to intensively interactâ€ if there were gap of number of male and female students.